PENGARUH STRUKTUR KEPEMILIKAN MANAJERIAL, UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA DENGAN KOMITE AUDIT SEBAGAI VARIABEL INTERVENING - Muhammad Rofiq Sunarko, Intan Dewi, Rispantyo & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2016)
The purpose of this research was: 1) analyzes the significance of the influence of managerial ownership structure, the size of the company and the audit committee of the company's management against earnings on construction and real estate in Indonesia stock exchange. 2) Analyzing the significance of the effect of the mediation of the audit committee on the effect of managerial ownership structure and the size of the company towards the management of profits on construction and services real estate company in Indonesia stock exchange. Research methods using case studies, qualitative and quantitative data, the source data used and secondary data. Technique of data analysis used a classic assumption test and path analysis. The research results obtained conclusions: 1) there are no significant influence managerial and ownership structure of the company against the size of the audit committee on the company's construction and real estate in Indonesia stock exchange. 2) there is a significant influence of managerial ownership structure, the size of the company and the audit committee of the company's management against earnings on construction and real estate in Indonesia stock exchange. 3) audit Committee mediate the influence of managerial ownership structure and the size of the company towards the management of profits on construction and services company real estate in Indonesia stock exchange.Keywords: managerial ownership structure, the size of the company, the audit committee, earning management.